PROFESIONALISME GURU FIQIH DALAM PEMBELAJARAN DAN IMPLIKASINYA TERHADAP SIKAP KEBERAGAMAAN SISWA DI MTS NEGERI KOTA MANADO - Huda, Muhamad Nuril (LP2M IAIN Jember, 2020)
Teacher professionalism is something that cannot be negotiated, including for a fiqh teacher. Because the professionalism of a teacher plays a very dominant role, even though the sophistication of technology is very, very impressive. There are still too many human elements such as attitudes, value systems, feelings, motivation, habits, etc. which are expected to be the result of the learning process. A good religious attitude is one of the hopes that results from a fiqh study. And only fiqh learning managed by a professional fiqh teacher has implications for the formation of students' religious attitudes. Professional fiqh teachers are able to create a dynamic and democratic learning atmosphere, and will have implications for students' religious attitudes in the form of; first, the students will understand what they do and at the same time understand what other people who are different from it have been practicing, Second, the level of student obedience in carrying out religious rites is getting better, Third, the more students have more confidence in the truth of their religion, Fourth, the students' commitment to godliness is getting better. good, and Fifth, embedded tolerance towards all differences. Profesionalisme guru adalah suatu hal yang tidak dapat ditawar-tawar lagi, termasuk bagi seorang guru fiqih. Karena keprofesionalan seorang guru memegang peranan yang sangat dominan, meskipun kecanggihan tehnologi sudah amat sangat mengagumkan. Masih terlalu banyak unsur-unsur manusiawi seperti sikap, sistem nilai, perasaan, motivasi, kebiasaan, dan lain-lain yang diharapkan menjadi hasil dari proses pembelajaran. Sikap keberagamaan yang baik adalah salah satu harapan yang dihasilkan dari sebuah pembelajaran fiqih. Dan hanya pembelajaran fiqih yang dikelola oleh seorang guru fiqih profesional yang memungkinkan berimplikasi pada pembentukan sikap keberagamaan siswa. Guru fiqih yang profesional mampu menciptakan suasana pembelajaran yang dinamis dan demokratis, dan akan berimplikasi terhadap sikap keberagamaan siswa berupa; pertama siswa akan memahami apa yang diamalkan sekaligus memahami apa yang selama ini diamalkan orang lain yang berbeda dengannya, Kedua, tingkat kepatuhan siswa dalam menjalankan ritus-ritus agama semakin baik, Ketiga, semakin tambah keyakinan siswa terhadap kebenaran agamanya, Keempat, komitmen kebertuhanan siswa semakin baik, dan Kelima, tertanam sikap toleransi terhadap segala perbedaan..